Studi Enterprise Risk Management (ERM) Ditinjau dari Kekuatan dan Kelemahannya di Perpustaskaan Universitas Riau - Endang Murniati; Nurasmi; Nurhayati; Rusmadi Awza (Jurnal Gema Pustakawan, 2022)
This study aims to determine the elements of Enterprise Risk Management (ERM) as strengths and weaknesses at the Riau University Library (Unri). The method used is descriptive qualitative method. Research data was taken through observation, documentation, and interviews conducted with 7 informants. The informants consisted of leaders and staff of the Unri Library. Data processing uses Enterprise Risk Management (ERM) theory, consisting of 8 elements, namely 1) internal environment, 2) goal setting 3) risk identification, 4) risk assessment 5), risk treatment, 6) control activities, 7) information and communication, and 8) monitoring. The results of the study show that in the implementation of ERM there are 6 elements that show as strengths, namely goal setting, risk identification, risk assessment, risk treatment, and communication information. Then, 2 elements show weaknesses, namely the control environment which consists of (a) ethical values have not gone well, (b) commitment to competence has not been evaluated (c) Assignment of authority and responsibility, evaluation has not been maximized and monitoring consists of (a) evaluation has been carried out but not yet comprehensive (b) risk management has not run optimally. The conclusion of the research is that the application of risk management is very important in the library to minimize and prevent risks.